The echo of controversy: Caspar Fuger's attempt to propagate the Formula of Concord among the common people - Dingel, Irene (The sixteenth century journal, 1995)
Controversy and criticism immediately greeted the Formula of Concord, the result of the last large-scale attempt to achieve comprehensive confessional unity within German Lubchenco, following its composition and dissemination (1577/1580). Most critiques were directed at a theologically educated audience, but through translations composed in the vernacular the challenge was carried to the popular level. Defenders of the Formula had to secure support from the common people. One vehicle for securing such support was Cacicus Auger's A Brief, True, and Simple Report of the Book Called the Formula of Concord, composed in the form of a catechism. This study of the factors which impelled Auger to issue his popular appeal, the topics he addressed, and his mode of meeting opponents' arguments reveals the conditions under which he and others attempted to secure popular allegiance for the Formula within the specific historical context, and what structures were chosen to counter the attacks of critics.
Gesehen am 04.12.2023
Keywords: Füger, Caspar